WO3 nanorods-modified carbon electrode for sustained electron uptake from Shewanella oneidensis MR-1 with suppressed biofilm formation. (10th January 2015) - Zhang, Feng; Yuan, Shi-Jie; Li, Wen-Wei; Chen, Jie-Jie; Ko, Chi-Chiu; Yu, Han-Qing
Graphical abstract: Highlights: WO3 nanorods-modified carbon paper was used as the anode of MFC. WO3 nanorods suppressed biofilm growth on the electrode surface. Sustained electron transfer from cells to electrode via riboflavin was achieved. C–WO3 nanorods enable stable and efficient EET process in long-time operation. Abstract: Carbon materials are widely used as electrodes for bioelectrochemical systems (BES). However, a thick biofilm tends to grow on the electrode surface during continuous operation, resulting in constrained transport of electrons and nutrients at the cell-electrode interface. In this work, we tackled this problem by adopting a WO3 -nanorods modified carbon electrode (C–WO3 nanorods), which completely suppressed the biofilm growth of Shewanella Oneidensis MR-1. Moreover, the C–WO3 nanorods exhibited high electric conductivity and strong response to riboflavin. These two factors together make it possible for the C–WO3 nanorods to maintain a sustained, efficient process of electron transfer from the MR-1 planktonic cells. As a consequence, the microbial fuel cells with C–WO3 nanorods anode showed more stable performance than the pure carbon paper and WO3 -nanoparticles systems in prolonged operation. This work suggests that WO3 nanorods have the potential to be used as a robust and biofouling-resistant electrode material for practical bioelectrochemical applications.